EQUIPAMIENTO SOLAR SUSTENTABLE PARA EL ESPACIO PUBLICO - Vera, Luis; Pilar, Claudia (Anais Congresso Brasileiro de Energia Solar - CBENS, 2022)
This article presents the results of the technological design, manufacture, assembly and evaluation of use, sustainable solar equipment for public space. The general objective is the design of equipment powered by solar energy to promote the use of renewable energies in the community. For this, aesthetically pleasing technological devices were designed, with low maintenance, high durability, with anti-vandalism criteria, portable and easy to assemble and install, materialized through components available in the regional market. The hypothesis that guides this research and development project is that for the population to accept renewable energies it has to interact with them, for example, from the satisfaction of daily needs. A valid alternative to promote this interaction are the equipment for public and community use, using materials available in the region such as metal and wood, and integrating different functions in a single device. For the design, the premises of Design Thinking (DT) were implemented in two design lines: one made of metal (called EUsolar) and another in wood (called IRU). In both cases they are Autonomous Photovoltaic Systems with designs of bus stops, stalls and solar chargers. The solar charger of each of these lines was manufactured and assembled in public spaces in the Northeast Region of Argentina (NEA), which allowed to verify the prototypes in real conditions of use. To know the perception of users, an anonymous survey was carried out that resulted in a high valuation of the initiative in terms of its usefulness, its aesthetics and the application of renewable energy in public facilities.